Rantes - A New Target For Fighting Against HIV Infection - KIRTI WASNIK, (International Journal of Pharma and Bio Sciences, 2011)
Although treatments for AIDS and HIV can slow the course of the disease, there is currently no vaccine or cure. Antiretroviral treatment reduces both the mortality and the morbidity of HIV infection, but these drugs are expensive and routine access to antiretroviral medication is not available in all countries. Due to the difficulty in treating HIV infection, preventing infection is a key aim in controlling the AIDS pandemic, with health organizations promoting safe sex and needle-exchange programmes in attempts to slow the spread of the virus. RANTES was shown to be the most potent member of a trio of CC chemokines released by CD8+ T cells that were able to suppress the replication of non-syncitium-inducing (NSI) HIV-1 strains in vitro the others were macrophage inflammatory protein 1 α (MIP-1α) and MIP-1β. Some studies in vivo have supported a role for RANTES in HIV suppression, with the demonstration of unusually high levels of RANTES production in both HIV exposed humans and vaccinated monkeys who appear to be resistant to infection with HIV or simian immunodeficiency virus (SIV). These encouraging observations have led to further studies to test the potential therapeutic use of RANTES, both in the treatment and prevention of HIV infection.